Integrative Biochemical Adaptations to Concurrent Heat Stress and Physical Exertion in Humans - OKOH, Frank; NWABUWE, Sunday Nathaniel (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2025)
As global temperatures continue to rise, athletes are increasingly exposed to environments where physical exertion is compounded by extreme heat stress. This study investigated the integrative biochemical adaptations that occur in response to simultaneous thermal and exercise stress in trained endurance athletes. Using a randomized crossover design, thirty male athletes completed treadmill running trials at 70% VO₂max for 60 minutes under thermoneutral (22°C) and heated (40°C) conditions. Blood and muscle samples were collected pre-exercise, post-exercise, and during recovery to assess levels of heat shock proteins (HSP70, HSP90), oxidative stress markers (ROS, MDA), antioxidant enzymes (SOD, GPx), inflammatory cytokines (IL-6, TNF-α), and mitochondrial regulators (PGC-1α, citrate synthase). Results showed significantly elevated HSP70 (+70%), MDA (+60%), and inflammatory cytokines in the heat condition compared to thermoneutral trials (p < 0.01). Antioxidant responses and mitochondrial gene expression also increased, indicating adaptive mechanisms to mitigate cellular damage. However, the heat trial was associated with higher core temperature, perceived exertion, and lactate accumulation, highlighting increased physiological strain. These findings suggest that concurrent heat and exercise stress evoke complex biochemical responses that can either support performance through adaptation or hinder it through systemic overload. The study highlights the importance of heat acclimatization, antioxidant support, and biochemical monitoring in optimizing performance and protecting athlete health in hot environments.